Cubic interpolated pseudo particle (CIP) - Lattice Boltzmann scheme for the simulation of lid-driven cavity flow - Dany Ak, Dominic Neng (2010)
In this thesis, the Cubic Interpolated Pseudo Particle (CIP)-Lattice Boltzmann Model (LBM) scheme is applied for the simulation of lid driven flow for deep cavities. The thesis describe on how the advection term in the lattice Boltzmann equation is discretise and solved using CIP. The CIP which is similar to the form of finite difference method is known as numerical method for solving advection equations with low numerical diffusion. The obtained results feature the flow in deep lid driven cavity, in which the streamlines, the dynamics of primary vortices and corner vortices, and the velocity profile are investigated and compared with previous study from experiment and theory. By coupled the CIP and LBM, good agreement is obtained for the present study with those previous study using original LBM.